Merger efficiency and welfare implications of buyer power - Özlem Bedre-Defolie; Stéphane Caprice (Deutsches Institut für Wirtschaftsforschung (DIW), 2011)
This paper analyzes the welfare implications of buyer mergers, which are mergers between downstream firms from different markets. We focus on the interaction between the merger's effects on downstream efficiency and on buyer power in a setup where one manufacturer with a non-linear cost function sells to two locally competitive retail markets. We show that size discounts for the merged entity has no impact on consumer prices or on smaller retailers, unless the merger affects the downstream efficiency of the merging parties. When the upstream cost function is convex, we find that there are waterbed effects, that is, each small retailer pays a higher average tariff if a buyer merger improves downstream efficiency. We obtain the opposite results, anti-waterbed effects, if the merger is inefficient. When the cost function is concave, there are only anti-waterbed effects. In each retail market, the merger decreases the final price if and only if it improves the efficiency of the merging parties, regardless of its impact on the average tariff of small retailers.
Keywords: D43; K21; L42; 330; buyer mergers; non-linear supply contracts; merger effciencies; size discounts; waterbed effects; Übernahme; Lieferanten-Kunden-Beziehung; Nachfragemacht; Wirtschaftliche Effizienz; Kostenfunktion; Theorie